Effect of Wet Cupping Therapy (Raktamoksha) in the Management of Carpal Tunnel Syndrome: A Pre-Post Test Design (International Journal of Ayurveda and Pharma Research, 2025)
Background and objective: Carpal tunnel syndrome (CTS) affects approximately 4.25% of the global adult population, with women aged 30–60 years having a threefold higher risk compared to men. CTS primarily manifests as pain, tingling, numbness, and paraesthesia in the thumb, index, middle, and lateral half of the ring finger, with nocturnal exacerbation often relieved by shaking the hands. If untreated, CTS may cause permanent median nerve damage, leading to irreversible numbness, thumb deformity, and muscle atrophy. While surgical interventions provide symptom relief, they carry risks of recurrence, intraoperative complications, and wrist instability. This study aimed to evaluate Raktamokṣa by cupping therapy as a potential alternative or adjunctive treatment for CTS. Methodology: A single-group pre-post-test design was conducted at AVCH Kottakkal with 30 CTS-diagnosed participants. Wet cupping therapy was administered on day 1 and day 16. Assessments were done on days 1, 8, 16, 25, and 45 using the Boston Carpal Tunnel Questionnaire and clinical signs and symptoms. Data were analyzed using Friedman test, McNemar test, and Wilcoxon Signed Rank test. Results and discussion: Wet cupping therapy significantly reduced CTS signs and symptoms (p < 0.05). However, no significant changes were observed in nerve conduction velocity studies. Conclusion: Wet cupping therapy in two sittings showed statistically significant improvement in CTS symptoms, supporting the rejection of the null hypothesis and acceptance of the alternative hypothesis regarding its efficacy.